Finance and Development, December 1970. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1970)
This paper describes problems and prospects associated with urbanization. The paper sees the rapid urbanization in the less developed world not as a crisis that can be 'dealt with' by urgent measures but as a major historical phenomenon that calls for analytical study as well as current action in the hope that it can be influenced to play a positive role in economic development. The paper also analyzes the exchange rates at the beginning of the 1970s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet